Some theoretical considerations on behavioral changes and their use in housing project evaluation - Munarriz, Mayu T. (1987)
Behavioral changes may be used to evaluate government development projects. Behavioral change is the change in man's generalized character and actions as a result of changes in income, evaluation, land ownership and degree of urbanization. Different ways of affecting behavioral change were examined and a simple model for inducing behavioral change from a traditional to a modern direction is formulated.
Keywords: Community development projects -- Moral and ethical aspects; Public housing aspects -- Social aspects